Penetrating neck trauma with section of the thyrohyoid membrane. Case report - Camacho Apaza, Johnny; Claros Coca, Zenia; Mollo Poma, Adriano (Cirugía del Uruguay, 2024)
Penetrating neck trauma is an emergency that challenges the surgeon from initial evaluation to definitive management. The case of a 24-year-old female patient with a transverse penetrating neck injury is presented, with air escaping through the injury site along with active bleeding, requiring a definitive airway and hemorrhage control in the initial management; with emergency surgical admission, with findings of: section of the thyrohyoid membrane at the level of the upper edge of the thyroid cartilage, epiglottis and both anterior jugular veins.The behavior was repair by planes, from the depths to the surface. The experience acquired in the management of this case allows us to highlight that following the life support guidelines together with definitive surgical trauma care in less than 24 hours in the event of penetrating neck trauma increases the probability of success in management and evolution.